IMPLEMENTASI DAN EKSISTENSI HUKUMAN DISIPLIN BAGI NARAPIDANA PERIODE 2023 (STUDI KASUS DI RUMAH TAHANAN NEGARA KELAS I CIPINANG) - Cipto Pasaribu, Candra; Rahmat, Diding (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2024)
Law enforcement is very necessary in handling violations of disciplinary regulations for correctional inmates. "The aim of disciplinary punishment as a form of administrative sanction is to correct and educate correctional inmates who commit disciplinary violations. In the problem formulation of this thesis, this is the Disciplinary Punishment Policy for Prisoners in Indonesia and the Implementation and Existence of Disciplinary Punishment for Prisoners in the Cipinang Class I Detention Center. The data analysis method used is a qualitative analysis method, namely by exploring and comparing the implementation of laws and regulations in practice. The results of this research are: In its implementation, the appropriate procedures for implementing administrative sanctions for correctional inmates are focused on correctional officers who must be required to re-examine correctional inmates in accordance with the flow of the disciplinary violation mechanism, with the aim of finding out violations that have been committed. For disciplinary violators If a prisoner commits a light level disciplinary sanction, the disciplinary sanction will be given in the form of a Warning. For medium level disciplinary violators, the disciplinary sanction given will be in the form of a postponement of the visit, and for serious disciplinary violations for prisoners suspected of committing a serious violation, an inspection will be carried out by an officer. , then the results of the examination will be used as recommendation material for carrying out the TPP trial, then the results of the TPP trial will be submitted to the Head of the Detention Center as a consideration for imposing disciplinary sanctions. My suggestion is that the Cipinang Class I Detention Center be more strict in implementing disciplinary sanctions/punishments against inmates who violate the detention center rules as regulated in Law Number 22 of 2022 concerning Corrections and Regulation of the Minister of Law and Human Rights Number 6 2013 concerning the Rules of Procedure for Correctional Institutions and State Detention Centers so that it can have a deterrent effect on residents of correctional institutions so that they no longer violate the rules and regulations of prisons.